Sensationalism in argumentation: a case of the Zimbabwean parliament debates - Jakaza, Ernest (Stellenbosch Papers in Linguistics Plus, 2019)
Parliamentary debates are an argumentative interaction in which Members of Parliament (MPs) employ varied language devices in order to win debates in their favour. However, in an effort to win the debate at all costs, some parliamentarians seem to sensationalise their arguments in order to win favour or support from both internal and external audiences - the rationale judge. Sensationalism in argumentation is a presentation of an argument in a specific way in order to appeal to the hearer or the other participant’s emotions or feelings. This article examines the role of sensationalism in argumentation, drawing its examples from the Zimbabwean parliamentary debates. The study is qualitative in nature, utilising a case study research design. It is couched in the Extended Pragma-Dialectic Theory of Argumentation. Debates from the Zimbabwean parliament are purposively sampled and the analysis is based on the argumentation theoretical framework. The article concludes that the main function of sensationalist language in parliamentary argumentation is rhetorical rather than dialectic. Arguers utilise sensationalist language to convince and win the debate in their favour. The use of sensationalism as an argumentative move is misused or abused, as it is a fallacious move.